THE INFLUENCE OF INSTAGRAM AND AUDITORY LEARNING STYLE ON GERMAN LANGUAGE MASTERY IN STUDENTS OF SMAN 1 MAROS - Malik, Agung Rinlady (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This study aims to determine the influence of Instagram and auditory learning styles on mastery of students' German vocabulary. This research is a quantitative research with an experimental method. The study sample used random sampling so that two groups of samples could be determined in Class XI of SMA 1 Maros, namely class XI IPA 1 as the experimental class and XI IPA 2 as the control class. The results of this study indicate: that there is a significant influence on the mastery of German in the group of students using instagram in learning. The results of the analysis show that Q count = 7.77. From the Critical Values ??Of Q (Tukey) table with ? = 0.05, k = 4 and n = 11 it is known the value of Q table (0.05; 4; 11) = 4.26. Because Q count = 4.33> Q table = 4.26 or H 0 is rejected, then the mastery of the German language group of students who were given the Instagram learning strategy and who had auditory style (30.90) than the group of students who were given conventional learning strategies (29.63) and those who have auditory learning styles.